2020
DOI: 10.1016/j.ejca.2020.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Association of premenopausal risk-reducing salpingo-oophorectomy with breast cancer risk in BRCA1/2 mutation carriers: Maximising bias-reduction

Abstract: Background: Whether risk-reducing salpingo-oophorectomy (RRSO) in BRCA1/2 carriers reduces the breast cancer (BC) risk is conflicting, potentially due to methodological issues of prior analysis. We analysed the association between premenopausal RRSO and BC risk in BRCA1/2 carriers after adjusting for potential biases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“…A 2020 study including 853 premenopausal carriers of a pathogenic BRCA1/2 variant showed that premenopausal RRSO decreased breast cancer risk in BRCA1 pathogenic variant carriers (HR, 0.45; 95% CI, 0.22-0.92), but not in BRCA2 pathogenic variant carriers (HR, 0.77; 95% CI, 0.35-1.67). 192 Analysis for this study began observation 6 months after genetic testing to avoid event-free time bias.…”
Section: Bilateral Salpingo-oophorectomymentioning
confidence: 99%
“…A 2020 study including 853 premenopausal carriers of a pathogenic BRCA1/2 variant showed that premenopausal RRSO decreased breast cancer risk in BRCA1 pathogenic variant carriers (HR, 0.45; 95% CI, 0.22-0.92), but not in BRCA2 pathogenic variant carriers (HR, 0.77; 95% CI, 0.35-1.67). 192 Analysis for this study began observation 6 months after genetic testing to avoid event-free time bias.…”
Section: Bilateral Salpingo-oophorectomymentioning
confidence: 99%
“…Evidence for an association between rrBSO and breast cancer risk is based on observational studies (3,(4)(5)(6)(7)(8)(9)(10)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43), which contain inherent biases that must be considered when interpreting their results and applying them to clinical practice. These biases have been discussed since 2003 (see Table 2; refs.…”
Section: Types Of Bias In Observational Studies Of Rrbso and Breast Cancer Riskmentioning
confidence: 99%
“…Risk-reducing bilateral salpingo-oophorectomy (rrBSO) is highly effective at reducing the risk of tuboovarian cancer (2)(3). In contrast, the role of rrBSO in mitigating breast cancer risk in mutation carriers, while previously widely accepted and incorporated in clinical guidelines (see Table 1), is now less clear and challenged by emerging contradictory evidence (4)(5)(6)(7)(8)(9)(10). This article reviews the literature on rrBSO and subsequent risk of first breast cancer for mutation carriers and suggests modifications to existing guidelines based on compilation of new evidence from recent studies.…”
Section: Introductionmentioning
confidence: 99%
“…Die durchschnittliche Operationszeit für eine RRSO ohne peritoneale Biopsie betrug 64,3 Minuten verglichen mit 77,8 Minuten für eine RSSO mit peritonealer Biopsie. Das kam einer statistisch signifikanten Verlängerung der Operationszeit von 16 % gleich (13,5 Minuten, p = 0,0383).…”
Section: Objectiveunclassified
“…Due to ineffective screening programs for OC, risk reducing bilateral salpingo-oophorectomy (RRSO) is suggested for gBRCA1/2 -mutation carriers 3 .The goal is to undergo RRSO as late as possible to reduce side effects caused by iatrogenic menopause and premature ovarian failure (POF) but early enough to prevent OC. At the moment, according to international guidelines RRSO is recommended between the age of 35 and 40 for gBRCA1 mutation carriers and between the age of 40 and 45 for gBRCA2 mutation carriers but at least 5 years before the first diagnosis of OC in the family occurred 3 , 5 . These recommendations are based on individual risk calculation with the Breast and Ovarian Analysis of Disease Incidence and Carrier Estimation Algorithm (BOADICEA), a validated calculation program for cancer risks 6 , 7 .…”
Section: Objectivementioning
confidence: 99%